Borrelia - host interactions: zoom in on the big picture. - Strnad, Martin (Jihočeská univerzita, 2021)
The thesis was written with the intention to bring together cutting-edge imaging methods and applications in order to illustrate how imaging can answer pathogenesis-related questions in Lyme disease at various resolution scale. Correlative light and electron microscopy, atomic force microscopy-based single-molecule force spectroscopy and solution nuclear magnetic resonance have been used to shed light on the underlying mechanisms associated with Lyme disease Borrelia infection. Specifically, the key molecular players and interactions responsible for the variance in the pathogenicity and disease outcome of Borrelia species have been studied. The rationale behind such studies was highlighted by review articles, which are part of the thesis.
Borrelia - host interactions: zoom in on the big picture.
Keywords: microscopy; borrelia; diversity; lyme disease; adhesins; microscopy; borrelia; diversity; lyme disease; adhesins